PERKEMBANGAN ILMU MANAJEMEN: DITINJAU DARI ILMU FILSAFAT - Arif Fakhrudin; Imamudin Yuliadi (Jurnal Manajemen Dirgantara, 2023)
Philosophically, management is a collection of knowledge and beliefs that provide a basis for determining solutions to managerial problems. Every science cannot be separated from philosophy because philosophy is the root of all human knowledge, both scientific and non-scientific knowledge. Management philosophy and science have a close correlation. The practice and science of management has a very deep philosophical dimension. Management cannot be separated from philosophy because without philosophy management does not have a strong foundation. Based on the philosophy of science from an ontological perspective, the essence of management theory in business organizations is a science that offers a management process so that business organizations can achieve their goals. The final goal to be achieved through this management process is the achievement or fulfillment of the goals that have been set. Based on an epistemological point of view, management theory in business organizations introduces methods or ways of making decisions or solving problems that can be used by managers in running business organizations. Apart from that, management science introduces various management theories to be practiced in business activities. In an axiological perspective, ethical values and social responsibility must be taken seriously in the application of management science to business organizations. In management theory, business orientation is not only about seeking profit but also paying attention to the norms that apply in society and paying attention to the interests and welfare of all parties. Because management theory has an ontological, epistemological and axiological perspective, management theory is actually a philosophy of science. Therefore, management theory needs to be developed to be applied in business organizations.